LANGUAGE, IDEOLOGY AND POWER RELATION REFLECTED IN THE HEADLINES NEWS OF THE JAKARTA POST AND THE JAKARTA GLOBE - Winarni, Sri (2010)
The object of the research is the headlines news of The Jakarta Post and The Jakarta globe. The major problem of this study is how the language, ideology and power relation is reflected in headlines news The Jakarta Post and The Jakarta Globe. Therefore, the study analyzes the headlines news based on structural elements of the newspaper and analyzes social cognition and historical context. The type of this study is qualitative study. The writer uses two data sources: they are primary data sources and secondary data sources. The primary data sources and the object of the study are the headlines news itself. Meanwhile the secondary data sources are the other sources related to the primary data sources such as journal, and website about the newspaper. The method of the data collection is library research by collecting both primary and secondary data. The technique of data analysis is descriptive analysis based on critical discourse analysis.The result of the analysis shows the following conclusion: First language of The Jakarta Post and The Jakarta Globe express aspect ideology. Second, ideology of The Jakarta Post and The Jakarta Globe pragmatism that is the truth which meets the interests of the capital owner. Third, the power relation between both newspapers is the capital owner.